Radość, serdeczność, szczęście, wdzięczność, zadowolenie? Pozytywne emocje zwerbalizowane w wybranych, adresowanych do mnie, dedykacjach naukowych - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of this paper is the lingua-cultural reflections on positive emotions captured in dedications addressed to the author. These may be concise or more extensive, more or less conventionalized, often very personal texts, whose authors are scientists representing different scientific disciplines, different scientific generations and different scientific centers.
Keywords: emocje; edukacja; werbalizacja; badania językowo-kulturowe; komunikacja interpersonalna; emotions; education; verbalization; lingua-cultural studies; interpersonal communication